Ganoderiol F purified from Ganoderma leucocontextum retards cell cycle progression by inhibiting CDK4/CDK6 - Li, Xiangmin (Cell Cycle, 2019)
This study was designed to purify molecules possess anti-cancer cell activity from the fruit body of Ganoderma leucocontextum. Bio-activity-guided purification and chromatographic separation of Ganoderma leucocontextum extract led to the enrichment of bioactive fractions and isolation of a single compound. The purified compound was identified as Ganoderiol F, which induced cancer cell death. In the in vivo experiments, we founded ethanol extract and ethyl acetate fraction inhibited tumor growth in the mice injected with 4T1 cells. We found that Ganoderiol F-mediated suppression of breast cancer cell viability occurred through cell cycle arrest. Ganoderiol F down-regulated expression of cyclin D, CDK4, CDK6, cyclin E and CDK2 and inhibited cell cycle progression arresting the cells in G1 phase. In addition, Ganoderiol F up-regulated pro-apoptotic Foxo3, down-regulated anti-apoptotic c-Myc, Bcl-2 and Bcl-w leading to apoptosis in human breast cancer cells MDA-MB-231. These results showed that c-Myc, cyclin D-CDK4/CDK6 and cyclin E-CDK2 are the central components of Ganoderiol F regulation of cell cycle progression. Hence Ganoderiol F may serve as a potential CDK4/CDK6 inhibitor for breast cancer therapy. Abbreviations: GLE: Ganoderma leucocontextum ethanol extract; GLEA: Ganoderma leucocontextum ethyl acetate fraction; GLPE: Ganoderma leucocontextum petroleum ether fraction; RP-HPLC: reversed-phase high-performance liquid chromatograph; DMEM: Dulbecco’s modified Eagle’s medium; FBS: fetal bovine serum; PAGE: polyacrylamide gel electrophoresis.